Alcohol consumption by pregnant women attending antenatal clinics in two Mont-Amba health facilities, Kinshasa (DRC) - Katumpa, Bruno Kalala; Muzinga, A.; Mazoba , Tacite Kpanya; Lukunku, Kabambi A.; Zalagile, Pierre Akilimali; Mbanzulu, Pita-Nsoninzau Damien (Orapuh Journal, 2025)
Introduction Alcohol refers to any beverage containing ethanol. Its consumption represents a sociocultural phenomenon and is often associated with celebration and sharing. Prenatal exposure to alcohol can cause various disorders in the developing fetus. Purpose This study aimed to determine the prevalence of alcohol consumption and its associated sociodemographic factors among pregnant women in Kinshasa. Methods A survey was conducted among 527 pregnant women attending antenatal clinics in the Mont-Amba Health District (Kinshasa). Results Of the participants, 21.4% reported consuming alcohol during pregnancy. Among these, 53.1% consumed alcohol for pleasure, and 7.1% did so with the belief that it would make their baby vigorous. Additionally, 4.4% of respondents rejected the idea of weaning off alcohol. Single women were the primary consumers, and beer was the most commonly consumed alcoholic beverage. Women from all religious denominations reported alcohol consumption in varying proportions. Conclusion In this study population, alcohol consumption during pregnancy was common. Many pregnant women were unaware of the harmful effects of alcohol on the fetus. Alcohol consumption was observed across all religious affiliations, and few participants expressed willingness to abstain.